Development and Evaluation of the Thinking About Recovery Scale: Measure of Parent Posttraumatic Cognitions Following Children's Exposure to Trauma. Issue 1 (31st January 2018) - Schilpzand, Elizabeth J.; Conroy, Rowena; Anderson, Vicki; Alisic, Eva
Abstract: Researchers have recently suggested that parent posttraumatic appraisals potentially contribute to the development of posttraumatic stress in both parents and children following children's exposure to trauma. However, a single‐instrument, multidimensional measure of parent posttraumatic cognitions as they relate to their child's recovery has yet to be operationalized. This study described the development and evaluation of a parent‐report questionnaire of parent posttraumatic cognitions, designed to be used after a child's exposure to trauma. We generated an initial pool of items in reference to existing theories and subjected this list to an iterative process of item writing and revision. Items were subjected to expert review to maximize construct validity. The 33‐item Thinking About Recovery Scale (TARS), which measures three domains ( My child has been permanently damaged; The world is dangerous for my child; Parents should always promote avoidance ) demonstrated good internal consistency (Cronbach's α = .74‐88) and convergent validity ( r 2 range = .08‐.40) when piloted in a sample of 116 parents of children who had been exposed to a serious accidental injury. The TARS augments the available literature by providing a brief measure of parent posttraumatic cognitions, an area which is currently understudied in childhood posttraumatic stress and could have broad clinical and research use.